Bilateral Reflex Fluctuations during Rhythmic Movement of Remote Limb Pairs - Mezzarane, Rinaldo A.; Nakajima, Tsuyoshi; Zehr, E. Paul (Frontiers in Human Neuroscience, 2017)
The modulation of spinal cord excitability during rhythmic limb movement reflects the neuronal coordination underlying actions of the arms and legs . Integration of network activity in the spinal cord can be assessed by reflex variability between the limbs, an approach so far very little studied. The present work addresses this question by eliciting Hoffmann (H-) reflexes in both limbs to assess if common drive onto bilateral pools of motoneurons influence spinal cord excitability simultaneously or with a delay between sides. A cross-covariance (CCV) sequence between reflexes in both arms or legs was evaluated under conditions providing common drive bilaterally through voluntary muscle contraction and/or rhythmic movement of the remote limbs. For H-reflexes in the flexor carpi radialis (FCR) muscle, either contraction of the FCR or leg cycling induced significant reduction in the amplitude of the peak at the zero lag in the CCV sequence, indicating independent variations in spinal excitability between both sides. In contrast, for H-reflexes in the soleus muscle, arm cycling revealed no reduction in the amplitude of the peak in the CCV sequence at the zero lag. This suggests a more independent control of the arms compared with the legs. These results provide new insights into the organization of human limb control in rhythmic activity and the behavior of bilateral reflex fluctuations under different motor tasks. From a functional standpoint, changes in the co-variability might reflect dynamic adjustments in reflex excitability that are subsumed under more global control features during locomotion.